How to design the ask?: funding units vs. giving money - Epperson, Raphael; Diederich, Johannes; Goeschl, Timo (Management science, 2025)
Unit donations are an alternative fundraising scheme in which potential donors choose how many units of a charitable good to fund rather than just giving money. Based on evidence from an online experiment with 8,673 participants, we demonstrate that well-designed unit donation schemes can significantly boost giving above and beyond the standard money donation scheme. A decomposition of the underlying mechanisms shows patterns consistent with the conjecture that unit donations increase impact salience and leverage donors’ cognitive biases by changing the metric of the donation space. Managers need to weigh the potential fundraising benefits of a unit scheme against some important challenges, such as expert handling of the choice of unit sizes. - - This paper was accepted by Yan Chen, behavioral economics and decision analysis. - - Funding: Funding by Heidelberg University [Field of Focus IV under the Excellence Strategy] and the Austrian Science Fund [Grant SFB F63] is gratefully acknowledged. - - Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.00157.
Online veröffentlicht: 20. Juni 2024
Gesehen am 17.02.2025
Keywords: Aufsatz in Zeitschrift